2017
DOI: 10.1007/s12015-017-9799-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Erasing and Pancreatic Differentiation of Dermal Fibroblasts into Insulin-Producing Cells are Boosted by the Use of Low-Stiffness Substrate

Abstract: Several studies have demonstrated the possibility to revert differentiation process, reactivating hypermethylated genes and facilitating cell transition to a different lineage. Beside the epigenetic mechanisms driving cell conversion processes, growing evidences highlight the importance of mechanical forces in supporting cell plasticity and boosting differentiation. Here, we describe epigenetic erasing and conversion of dermal fibroblasts into insulin-producing cells (EpiCC), and demonstrate that the use of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Previous studies have reported that mechanical stretch or soft matrix significantly decreased the DNA methylation level of critical CG sites or specific genes (Vlaikou et al, 2017;Wang et al, 2017;Pennarossa et al, 2018), and non-CG methylation may regulate gene expression according to environmental changes (Patil et al, 2014). Our results were consistent with these reports that numerous DMRs and DMGs of mCG and non-CG methylation were identified in the stage (1-day/0 h) that environment-switched from 2D rigid to 3D soft (Figure 4A and Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that mechanical stretch or soft matrix significantly decreased the DNA methylation level of critical CG sites or specific genes (Vlaikou et al, 2017;Wang et al, 2017;Pennarossa et al, 2018), and non-CG methylation may regulate gene expression according to environmental changes (Patil et al, 2014). Our results were consistent with these reports that numerous DMRs and DMGs of mCG and non-CG methylation were identified in the stage (1-day/0 h) that environment-switched from 2D rigid to 3D soft (Figure 4A and Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the epigenetic erasing and conversion of dermal fibroblasts into insulin-producing cells was promoted by growing cells on low-stiffness substrates, which prevents stress fiber formation, and modulates YAP expression and distribution within cells [167].…”
Section: Directing Pancreatic Stem Cell Differentiation By Mechanotramentioning
confidence: 99%
“…Because of its powerful effects, 5-aza-CR induces global DNA hypomethylation (Christman, 2002) and gene reactivation (Jones, 1985) facilitating somatic cells switching from one phenotype to another (Glover et al, 1986;Harris et al, 2011;Taylor and Jones, 1979). A brief exposure to 5-aza-CR can convert adult skin fibroblasts and granulosa cells into different cell types Pennarossa et al, 2017Pennarossa et al, , 2014Pennarossa et al, , 2013. Such fate switch is not limited to cells belonging to the same embryonic layer but can also occur between cells belonging to different embryonic layers.…”
Section: Epigenetic Cell Conversionmentioning
confidence: 99%
“…These include reduced dimensions with large nuclei, global chromatin decondensation, as well as expression of pluripotencyrelated genes such as OCT4, NANOG, ZFP42 zinc finger protein (REX1) and SRY (sex determining region Y)-box 2 (SOX2). This was achieved not only with human and mouse but also with pig and dog fibroblasts Pennarossa et al, 2017Pennarossa et al, , 2014Pennarossa et al, , 2013 and the high efficiency and robustness of the process makes it the best option for working in domestic species .…”
Section: Epigenetic Cell Conversionmentioning
confidence: 99%